2019
DOI: 10.22159/ajpcr.2019.v12i9.34559
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bioactive Compounds in Flower of Tabernaemontana Divaricata (L.) Using Gas Chromatography–mass Spectrometry Analysis

Abstract: Objective: Herbs are a key resource with therapeutic properties. Nowadays, there is a focus on the identification of bioactive compounds with the ability to act against various disorders. Methods: In the present study, gas chromatography–mass spectrometry analysis was conducted to determine the occurrence of different phytochemical compounds in ethanolic flower extract of Tabernaemontana divaricata (L.). Results: The ethanol extract of flower revealed the presence of several bioactive compounds suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Also, 1-Heptatriacontanol (1.6%) was detected in essential oil of I. alopecuroides. 1-Heptatriacontanol an alcoholic compound exhibit anti-hypercholesterolemic, antioxidant, anti-inflammatory, anticancer and antimicrobial effect (Baskaran et al, 2015;Kalaimagal, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Also, 1-Heptatriacontanol (1.6%) was detected in essential oil of I. alopecuroides. 1-Heptatriacontanol an alcoholic compound exhibit anti-hypercholesterolemic, antioxidant, anti-inflammatory, anticancer and antimicrobial effect (Baskaran et al, 2015;Kalaimagal, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that diabetic beta cells produce reactive oxygen species (ROS), which are counteracted by the overexpression of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POX). Antioxidants protect beta cells from oxidative damage by scavenging the free radicals produced, thus preventing diabetes from developing [ 27 29 ]. In transgenic mice, overexpression of SOD has been shown to prevent the development of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen important bioactive compounds in the methanolic extract of T. divaricata flowers were selected due to their bioactive potential towards antitumor, antibacterial, and anti-inflammatory properties and to give better pharmacological activities [ 27 29 ]. These compounds, enlisted in Table 1 , are subjected to a theoretical in silico ADME prediction study using the Web tool, SwissADME ( http://www.sib.swiss ).…”
Section: Methodsmentioning
confidence: 99%
“…Many medications have been extracted from the broad variety of medicinal plants found in nature, and these plants are widely utilized for traditional medical purposes throughout [1]. Medicinal plants are important in treating human physiological diseases in systems such as Ayurveda, Homeopathy, Siddha, and Folkloric medicine [2].…”
Section: Introductionmentioning
confidence: 99%